Células-tronco mesenquimais na terapia de lesões tendíneas iatrogênicas de coelhos: obtenção, aspectos histológicos e ultraestruturais - SOUZA, Luiz Augusto de (2012)
Most tendon injuries are related to trauma and involve partial or complete tendon section due to the action of cutting or sharp objects or laceration. Recently, medical advances have shown a growing interest in the use of cell therapy for the treatment of chronic and degenerative diseases with slow and ineffective healing. The aim of this study was to establish a protocol for mononuclear cells isolation from bone marrow (BM) of rabbits, followed by purification using negative depletion with the monoclonal antibody CD45 for separation of mesenchymal stem cells (MSCs), with further cultivation in MesenCult ® medium. After that, it was evaluated the effects of allogeneic transplantation of MSCs with or without collagen extracellular matrix (CEM) on wound healing of the common calcaneal tendon in rabbits after partial tenectomy. Clinical, physical, macroscopic, histological and electron microscopy evaluations of tendon fibers were conducted. It was concluded that the collection, isolation, purification and rapid expansion of MSCs obtained from the mononuclear fraction of BM can be achieved using the density gradient Ficoll-paque®, negative depletion of haematopoietic cells in immunomagnetic base and MesenCult® medium. Furthermore, it was noticed that the number of passages exerts a negative influence on the morphology of the cells. Regarding treatment of tendinous injuries, the group treated with MSCs from bone marrow cultured in MesenCult® soaked in collagen sponge showed better results in terms of progress and quality of healing with deposition of collagen fibers in longitudinal orientation.